ON THE NOTION OF THE MONSTROUS IN KANT’S CRITICAL PHILOSOPHY - Arriagada, Patricio; Ibarra B., Victor (Revista de Historia Social y de las Mentalidades, 2021)
This article discusses the aesthetical category of the monstrous, which is usually used to represent perpetrators. We believe that the monstrous does not properly approach the object that is meant to qualify, insofar as –from a philosophical-political point of view– when we say of someone that it is a monster, we say that he, she, or they exceed our capacity of understanding. We will show this deficiency through an analysis of this problem in Immanuel Kant’s philosophy to demonstrate that to reduction of the perpetrator to the monstrous has a very limited political performance